SPIRITUAL BASIS OF NATURE PROTECTION (Archive of Conferences, 2021)
The article provides a scientific analysis of the spiritual foundations of nature conservation. Human development depends on the environment, the consumption of high-quality, high-calorie, vitamin-rich food and other factors. In short, when a new generation is born, it is important to adhere to environmental standards.